2012
DOI: 10.1016/j.jjcc.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic retroperitoneal fibrosis, inflammatory aortic aneurysm, and inflammatory pericarditis—Retrospective analysis of 11 case histories

Abstract: Retroperitoneal fibrosis, inflammatory aortic aneurysm, and pericardial and mediastinal fibrosis are characterized by infiltration of immuno-inflammatory cells and deposition of thickened fibrous tissues. Several recent studies suggested that an immunoglobulin-G4 (IgG4)-related immunological mechanism may play a role in these diseases. By searching the clinical database of patients admitted to our department between 2000 and 2010, we summarized the clinical data of 11 patients who were diagnosed to have these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 21 publications
4
63
0
Order By: Relevance
“…Our literature review found two patients from seven reported cases with IgG4-related pericarditis who did not demonstrate fibrosis in the pericardium (Table) (4,7,9,10,12,13). In addition, four reported patients with IgG4-related pericarditis were not pathologically diagnosed with a pericardial specimen, such as in the present case (Table).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our literature review found two patients from seven reported cases with IgG4-related pericarditis who did not demonstrate fibrosis in the pericardium (Table) (4,7,9,10,12,13). In addition, four reported patients with IgG4-related pericarditis were not pathologically diagnosed with a pericardial specimen, such as in the present case (Table).…”
Section: Discussionsupporting
confidence: 48%
“…This indicates that not only the pathological but also the clinical presentation of IgG4-RD may be distinct among the tissues involved. Accordingly, IgG4-related pericardial disease is mostly characterized by fibrosis of the thickened pericardium and clinical presentation of constrictive pericarditis; however, one report has described acute inflammatory pathology in the pericardium (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, however, it has been reported that IgG4-related pathologies may be present in less than 60% in idiopathic retroperitoneal fibrosis (17,18). In addition, IgG4-positivity may not influence the clinical pictures and therapeutic responsiveness in idiopathic retroperitoneal fibrosis (19). Furthermore, a possible relationship between IgG4-related disease and carcinogenesis has been reported (20).…”
Section: Discussionmentioning
confidence: 99%
“…24) Mediastinal fibrosis and idiopathic retroperitoneal fibrosis can be associated with patients with IgG4-related pericarditis. 85,86) Idiopathic retroperitoneal fibrosis, the main symptom of which is hydronephrosis by ureteral encasement, is considered to be an IgG4-related disease, whereas secondary retroperitoneal fibrosis is caused by drugs, malignancy, infection, radiotherapy, and surgery. [87][88][89] Retroperitoneal fibrosis sometimes coexists with sclerosing pancreatitis.…”
Section: )mentioning
confidence: 99%
“…25) Cardiac and pleural effusion sometimes accompanies pericarditis, which could lead to a fatal outcome by causing respiratory insufficiency. 85) Echocardiography can detect it as highly echogenic thickening of the pericardium and cardiac effusion ( Figure 3A). CT imaging is also of help in the diagnosis ( Figure 3B).…”
Section: )mentioning
confidence: 99%